Perjalanan dan Proses Kreatif Seniman Rosid dalam Berkesenian - Neng Ulfah Sierra; Asep Miftahul Falah (ATRAT: Jurnal Seni Rupa, 2025)
This study describes the journey and creative process of an artist named Rosid in art using qualitative methods and the Graham Wallas approach. The purpose of this research is to understand how Rosid experiences and deals with the stages in his creative process, as explained by Graham Wallas’ theory. This study was conducted by conducting in-depth interviews and observations with Rosid, who focused on his experiences in creating and the creative processes he experienced. The results of the study show that Rosid’s creative process follows the stages described by Graham Wallas’ theory, namely preparation, incubation, illumination, and verification of reference sources to help form the concept of his artwork. Next. In the preparatory stage, Rosid gathers ideas, inspiration, and sources, in the incubation stage, he gives time for these ideas to “quietly” develop and interact subconsciously before being translated into concrete works. The illumination stage is the time when ideas that have “ripe” appear clearly in Rosid’s mind. This was the time when his creativity was at its peak, and he could clearly formulate concepts and visions for his work. The last stage, namely verification, involves checking and perfecting the work so that it is in accordance with Rosid’s initial vision. This research also reveals that Rosid’s life journey, including his personal experiences and interactions with his environment, played a role in shaping his creative process. The emotional and intellectual experiences Rosid has had in his life have contributed significantly to the richness and depth of his art.